The concise manual of apheresis therapy - Hanafusa, Norio; Noiri, Eisei (Springer Japan, 2014)
This pocket-sized manual serves as a concise and ideal reference work for therapeutic approaches using apheresis. Covering both basic theory and clinical details to facilitate improved treatment and patient outcomes, the text considers a variety of diseases, including myasthenia gravis, multiple sclerosis, Guillain-Barré syndrome, chronic inflammatory demyelinating polyneuropathy, nephrotic syndrome, TTP/TMA, dilated cardiomyopathy, and many other conditions. The book also reviews the growing trend toward adopting this unique therapy for a wide range of health management issues such as morbid obesity and/or type 2 diabetes, and for lowering LDL-cholesterol (cholesterol apheresis) in patients unresponsive to medication or lifestyle modification.